Incoming human papillomavirus 16 genome is lost in PML protein‐deficient HaCaT keratinocytes. (23rd January 2017) - Bienkowska‐Haba, Malgorzata; Luszczek, Wioleta; Keiffer, Timothy R.; Guion, Lucile G.M.; DiGiuseppe, Stephen; Scott, Rona S.; Sapp, Martin
Abstract: Human papillomaviruses (HPVs) target promyelocytic leukemia (PML) nuclear bodies (NBs) during infectious entry and PML protein is important for efficient transcription of incoming viral genome. However, the transcriptional down regulation was shown to be promoter‐independent in that heterologous promoters delivered by papillomavirus particles were also affected. To further investigate the role of PML protein in HPV entry, we used small hairpin RNA to knockdown PML protein in HaCaT keratinocytes. Confirming previous findings, PML knockdown in HaCaT cells reduced HPV16 transcript levels significantly following infectious entry without impairing binding and trafficking. However, when we quantified steady‐state levels of pseudogenomes in interphase cells, we found strongly reduced genome levels compared with parental HaCaT cells. Because nuclear delivery was comparable in both cell lines, we conclude that viral pseudogenome must be removed after successful nuclear delivery. Transcriptome analysis by gene array revealed that PML knockdown in clonal HaCaT cells was associated with a constitutive interferon response. Abrogation of JAK1/2 signaling prevented genome loss, however, did not restore viral transcription. In contrast, knockdown of PML protein in HeLa cells did not affect HPV genome delivery and transcription. HeLa cells are transformed by HPV18 oncogenes E6 and E7, which have been shown to interfere with the JAK/Stat signaling pathway. Our data imply that PML NBs protect incoming HPV genomes. Furthermore, they provide evidence that PML NBs are key regulators of the innate immune response in keratinocytes. IMPORTANCE: Promyelocytic leukemia nuclear bodies (PML NBs) are important for antiviral defense. Many DNA viruses target these subnuclear structures and reorganize them. Reorganization of PML NBs by viral proteins is important for establishment of infection. In contrast, HPVs require the presence of PML protein for efficient transcription of incoming viral genome. Our finding that PML protein prevents the loss of HPV genome following infection implies that the host cell may be able to recognize chromatinized HPV genome or the associated capsid proteins. A constitutively active interferon response in absence of PML protein suggests that PML NBs are key regulators of the innate immune response in keratinocytes.